Distinct miRNA expression patterns in circulating eosinophil subtypes and their subtype-derived exosomes in allergic asthma - Egle Vasyle; Andrius Januskevicius; Airidas Rimkunas; Jolita Palacionyte; Skaidrius Miliauskas; Kestutis Malakauskas (Inflammation Research, 2026)
Background Lung-resident (rEos) and inflammatory (iEos) eosinophil subtypes were initially characterized in mouse models of asthma and have been proposed to contribute differentially to inflammation and remodeling in human allergic asthma (AA). While microRNAs (miRNAs) and their transfer through exosomes may play important regulatory roles in immune signaling in asthma, miRNA profiles specific to eosinophil subtypes remain uncharacterized. This study aimed to identify distinct miRNA expression patterns in circulating eosinophil subtypes and subtype-derived exosomes from AA patients. Methods Peripheral blood iEos and rEos were isolated from 22 AA patients and 21 healthy subjects (HS). Next-generation sequencing (NGS) was used to identify differentially expressed miRNAs, and 16 candidates were subsequently selected for validation by quantitative polymerase chain reaction (qPCR) in eosinophil subtypes and in subtype-derived exosomes. Results NGS revealed 62 differentially expressed miRNAs in AA iEos and 35 in AA rEos compared with corresponding HS eosinophil subtypes. qPCR confirmed differential expression for 14 of 16 selected miRNAs in eosinophils or their exosomes between AA and HS. miRNA expressions distinguished AA from HS; furthermore, iEos and rEos showed distinct miRNA patterns within the AA group. Notably, AA rEos-derived exosomes showed greater miRNA enrichment than iEos-derived exosomes, implying active exosomal communication. Finally, validated miRNA patterns suggest a predominance of regulatory functions in rEos, whereas iEos displayed a profile consistent with pro-inflammatory activation. Conclusions This study provides molecular evidence that eosinophil subtypes are functionally specialized in AA. The differential miRNA patterns of rEos and iEos highlight their complementary regulatory and pro-inflammatory roles and suggest that eosinophil-derived miRNAs merit further investigation as potential biomarkers or modulators of airway inflammation.